PRINCIPALS’ CONFLICT MANAGEMENT STRATEGIES AND TEACHERS’ JOB PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN FCT, ABUJA, NIGERIA - Augustine , Kavwam Stanley (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This study examined the relationship between principals’ conflict management strategies and teachers’ job performance in public secondary schools in the Federal Capital Territory (FCT), Abuja, Nigeria. Method: The study adopted a descriptive survey research design. A sample of 240 teachers was selected using stratified random sampling. Data were collected through structured questionnaires measuring principals’ conflict management strategies and teachers’ job performance indicators. Descriptive statistical tools including frequencies and percentages were used for data analysis. Results: Findings revealed that principals employ multiple conflict management strategies, with collaborative problem solving, negotiation, and compromise being the most commonly perceived by teachers. The results further showed that effective conflict management significantly contributes to improved teacher performance by promoting a supportive work environment, reducing workplace tension, and strengthening professional relationships. Novelty: The study concludes that principals’ adoption of effective conflict management strategies plays a critical role in enhancing teachers’ job performance and sustaining organizational harmony in public secondary schools.